Air pollution impacts on in-hospital case-fatality rate of ischemic stroke patients - Keller, Karsten; Haghi, Seyed Hamed Rastguye; Hahad, Omar; Schmidtmann, Irene; Chowdhury, Sourangsu; Lelieveld, Jos; Münzel, Thomas; Hobohm, Lukas (Thrombosis research, 2023)
Background - A growing body of evidence suggests that air pollution exposure is associated with an increased risk for cardiovascular diseases. Data regarding the impact of long-term air pollution exposure on ischemic stroke mortality are sparse. - Methods - The German nationwide inpatient sample was used to analyse all cases of hospitalized patients with ischemic stroke in Germany 2015-2019, which were stratified according to their residency. Data of the German Federal Environmental Agency regarding average values of air pollutants were assessed from 2015 to 2019 at district-level. Data were combined and the impact of different air pollution parameters on in-hospital case-fatality was analyzed. - Results - Overall, 1,505,496 hospitalizations of patients with ischemic stroke (47.7% females; 67.4 % ≥70 years old) were counted in Germany 2015-2019, of whom 8.2 % died during hospitalization. When comparing patients with residency in federal districts with high vs. low long-term air pollution, enhanced levels of benzene (OR 1.082 [95%CI 1.034-1.132],P = 0.001), ozone (O3, OR 1.123 [95%CI 1.070-1.178],P < 0.001), nitric oxide (NO, OR 1.076 [95%CI 1.027-1.127],P = 0.002) and PM2.5 fine particulate matter concentrations (OR 1.126 [95%CI 1.074-1.180],P < 0.001) were significantly associated with increased case-fatality independent from age, sex, cardiovascular risk-factors, comorbidities, and revascularization treatments. Conversely, enhanced carbon monoxide, nitrogen dioxide, PM10, and sulphur dioxide (SO2) concentrations were not significantly associated with stroke mortality. However, SO2−concentrations were significantly associated with stroke-case-fatality rate of >8 % independent of residence area-type and area use (OR 1.518 [95%CI 1.012-2.278],P = 0.044). - Conclusion - Elevated long-term air pollution levels in residential areas in Germany, notably of benzene, O3, NO, SO2, and PM2.5, were associated with increased stroke mortality of patients. - Research in context - Evidence before this study: Besides typical, established risk factors, increasing evidence suggests that air pollution is an important and growing risk factor for stroke events, estimated to be responsible for approximately 14 % of all stroke-associated deaths. However, real-world data regarding the impact of long-term exposure to air pollution on stroke mortality are sparse. Added value of this study: The present study demonstrates that the long-term exposure to the air pollutants benzene, O3, NO, SO2 and PM2.5 are independently associated with increased case-fatality of hospitalized patients with ischemic stroke in Germany. Implications of all the available evidence: The results of our study support the urgent need to reduce the exposure to air pollution by tightening emission controls to reduce the stroke burden and stroke mortality.
Online verfügbar 22 March 2023, Version des Artikels 25 April 2023
Gesehen am 31.07.2023